Investigation of the nature and necessity of public audit as a vector of modernization of public administration and financial control in Ukraine - Долбнєва, Деніза Вадимівна (Technology audit and production reserves, 2017)
Economic nature and purpose of public audit are revealed in the article. Necessity and importance of establishment and functioning of the institution of public audit in Ukraine is proved as a prerequisite for modernization of the national system of public administration and financial control in order to ensure transparency, efficiency and economy of budgetary funds, state and municipal property, transparency and public accountability. Comprehensive approach to determining the nature and direction of public audit is proposed on the basis of systematization of international experience in this area and approaches of public audit, and also the conditions of its formation in our country are examined. Establishment of the institute of public audit in Ukraine will ensure the implementation of constitutional principles of the public authorities, an independent expert-analytical evaluation of effectiveness and efficiency of the public authorities and providing full, transparent and impartial information for general public about obtaining audit results; constant upgrading of systems and mechanisms of public administration and financial control; timely detection and prevention of violations of social values and interests, duties and tasks and others by officials.